Kecanduan TIKTOK Pada Anak Pesisir Pantai Dan Implikasi Layanan Konseling Kelompok (Studi Kasus) - widya syafitri harahap; Sona Satriana (Universitas Islam Negeri Sumatera Utara Medan, 2022)
The Tik Tok application is one of the social media applications that provides unique and interesting special effects to make short videos that are cool and attract the attention of many people who see it. The phenomenon of social media addiction to the Tik Tok application in students who like movement on the Tik Tok application compared to school assignments. . This research was conducted in Bagan Batu Village, Tanjung Beringin District, Serdang Begadai Regency. The research was conducted starting from February 12, 2022. The research subjects were MA students in Class X, totaling 5 students who were determined by purposive sampling technique. The problems experienced by 5 students are different, student I is caused by insecurity to other friends, student II is caused by dependence on others, student III is caused by a broken home (problems that occur from the family) student IV is due to being angry. angry and finally student V has learning difficulties because he is too dependent on the tik-tok application so he forgets the time and stays up all night as a result students have learning difficulties. The solution to this problem is to provide group counseling guidance services to students by providing advice in the form of examples and consequences when using the Tik-Tok application excessively by providing an understanding in order to minimize playing cellphones and then being replaced by being able to play with the closest people such as family, friends, and family. local living environment.